Instrumento para identificar las concepciones de los actores sociales sobre Educación Ambiental - Florez Cabrera, Jorge (UVserva, 2024)
El artículo devela el proceso de creación y validación de un instrumento enfocado en identificar las concepciones que tienen estudiantes, egresados y docentes acerca de la Educación Ambiental, Pensamiento Ambiental Latinoamericano, Ambiente y Cultura Ambiental, construida en el trasegar de la formación orientada en la Facultad de Educación de la Universidad Surcolombiana. El instrumento fue validado por ocho expertos con conocimientos ambientales, un (1) matemático estadístico y un (1) experto en evaluación para un total de diez expertos. La evaluación asignada por los expertos fue validada mediante el coeficiente alfa de Cronbach, calculado mediante la expresión: donde es el número de ítems, es la varianza total del instrumento y es la sumatoria de las varianzas de todos los ítems. Se concluyó que el instrumento validado es pertinente para realizar investigaciones acerca de concepciones relacionadas con las categorías enunciadas e inclusión de la dimensión ambiental. Instrument to identify the conceptions of social actors on Environmental Education Abstract: The article reveals the process of creation and validation of an instrument focused on identifying the conceptions that students, graduates and teachers have about Environmental Education, Latin American Environmental Thought, Environment and Environmental Culture, built in the transfer of oriented training in the Faculty of Education of the Surcolombiana University or autonomous training. Likewise, the instrument has a session focused on analyzing the trends of the participants in relation to the characteristics of the Inclusion of the Environmental Dimension. The instrument was created from the categories to be analyzed and was validated by eight experts with environmental knowledge, one (1) statistical mathematician and one (1) expert in evaluation for a total of ten experts. The assigned evaluation of the experts was validated by Cronbach's alpha coefficient, which was calculated using the expression: α=k/(k-1)∙(∑ S^2 p)/(S^2 t) where k is the number of items, S^2 t is the total variance of the instrument and ∑ S^2 p is the sum of the variances of all items. It was concluded that the validated instrument is relevant to conduct research on conceptions related to the stated categories and inclusion of the environmental dimension.